Cities and Mental Health - Gruebner, Oliver; Rapp, Michael A; Adli, Mazda; Kluge, Ulrike; Galea, Sandro; Heinz, Andreas (Deutsches Ärzteblatt international, 2017)
More than half of the global population currently lives in cities, with an increasing trend for further urbanization. Living in cities is associated with increased population density, traffic noise and pollution, but also with better access to health care and other commodities. This review is based on a selective literature search, providing an overview of the risk factors for mental illness in urban centers. Studies have shown that the risk for serious mental illness is generally higher in cities compared to rural areas. Epidemiological studies have associated growing up and living in cities with a considerably higher risk for schizophrenia. However, correlation is not causation and living in poverty can both contribute to and result from impairments associated with poor mental health. Social isolation and discrimination as well as poverty in the neighborhood contribute to the mental health burden while little is known about specific interactions between such factors and the built environment. Further insights on the interaction between spatial heterogeneity of neighborhood resources and socio-ecological factors is warranted and requires interdisciplinary research.